Prevalence of Brain Injuries and Recurrence of Seizures in Children With Posttraumatic Seizures. (10th April 2017) - Badawy, Mohamed K.; Dayan, Peter S.; Tunik, Michael G.; Nadel, Frances M.; Lillis, Kathleen A.; Miskin, Michelle; Borgialli, Dominic A.; Bachman, Michael C.; Atabaki, Shireen M.; Hoyle, John D.; Holmes, James F.; Kuppermann, Nathan; et al.
Abstract: Objectives: Computed tomography (CT) is often used in the emergency department (ED) evaluation of children with posttraumatic seizures (PTS); however, the frequency of traumatic brain injuries (TBIs) and short‐term seizure recurrence is lacking. Our main objective was to evaluate the frequency of TBIs on CT and short‐term seizure recurrence in children with PTS. We also aimed to determine the associations between the likelihood of TBI on CT with the timing of onset of PTS after the traumatic event and duration of PTS. Finally, we aimed to determine whether patients with normal CT scans and normal neurological examinations are safe for discharge from the ED. Methods: This was a planned secondary analysis from a prospective observational cohort study to derive and validate a neuroimaging decision rule for children after blunt head trauma at 25 EDs in the Pediatric Emergency Care Applied Research Network. We evaluated children < 18 years with head trauma and PTS between June 2004 and September 2006. We assessed TBI on CT, neurosurgical interventions, and recurrent seizures within 1 week. Patients discharged from the ED were contacted by telephone 1 week to 3 months later. Results: Of 42, 424 children enrolled, 536 (1.3%, 95% confidence interval [CI] = 1.2%–1.4%) had PTS. A total of 466 of 536 (86.9%, 95% CI = 83.8%–89.7%) underwent CT in the ED. TBIs on CT were identified in 72 (15.5%, 95% CI = 12.3%–19.1%), of whom 20 (27.8%, 95% CI = 17.9%–39.6%) underwent neurosurgical intervention and 15 (20.8%, 95% CI = 12.2%–32.0%) had recurrent seizures. Of the 464 without TBIs on CT (or no CTs performed), 457 had recurrent seizure status known, and five (1.1%, 95 CI = 0.4%–2.5%) had recurrent seizures; four of five presented with Glasgow Coma Scale scores < 15. None of the 464 underwent neurosurgical intervention. We found significant associations between likelihood of TBI on CT with longer time until the PTS after the traumatic event (p = 0.006) and longer duration of PTS (p < 0.001). Conclusions: Children with PTS have a high likelihood of TBI on CT, and those with TBI on CT frequently require neurosurgical interventions and frequently have recurrent seizures. Those without TBIs on CT, however, are at low risk of short‐term recurrent seizures, and none required neurosurgical interventions. Therefore, if CT‐negative and neurologically normal, patients with PTS may be safely considered for discharge from the ED.